Brain alterations and neurologic disorder progression induced by lymphatic dysfunction in the head and neck region - Hwayeong Cheon; Dong-Cheol Woo; Seungwoo Cha; Yeon Ji Chae; Inhee Maeng; Seung Jae Oh; Jae Yong Jeon (Acta Neuropathologica Communications)
Abstract The potential negative impact of lymphatic dysfunction caused by head and neck cancer treatment remains underexplored. Emerging evidence suggests that waste clearance and fluidic balance in the brain are connected to the peripheral lymphatic system in the head and neck region, implying that lymphatic injury in this area could contribute to brain damage. This study aimed to investigate the pathological alterations in the brain induced by peripheral lymphatic dysfunction in the head and neck region using the lymphatic obstruction animal model. An animal model underwent cervical lymph node dissection combined with radiation therapy to simulate the condition with the peripheral lymphatic dysfunction in the head and neck region after cancer treatment. Lymphatic drainage impairment in the head and neck region was associated with significant swelling, disrupted lymphatic drainage, and immune cell infiltration in the white matter. The imaging techniques revealed ventricular enlargement and increased brain water content caused by fluid imbalance leading to significant structural alterations in the brain. Histopathological analysis demonstrated structural brain alterations similar to that of hydrocephalus and cerebral edema, while rotarod tests showed a substantial decline in motor performance. These findings highlight the impact of peripheral lymphatic dysfunction on brain integrity and function. This study provides evidence that brain damage in head and neck cancer patients may be influenced not only by chemotherapy or radiotherapy but also by lymphatic dysfunction caused by surgical interventions. Lymphatic injury in the head and neck region emerges as a potential risk factor for brain damage, underscoring the need for further research into preventive and therapeutic strategies.